Pengenalan Hidroponik DFT (Deep Flow Technique) pada Tanaman Pakcoy (Brassica rapa L.) untuk Pencegahan Stunting di Desa Kuta Blang Kecamatan Samadua Kabupaten Aceh Selatan - Evi Julianita Harahap; Dewi Junita; Chairudin Chairudin; Agustinur Agustinur; Muhammad Afrillah (Universitas Teuku Umar, 2023)
Hydroponic Deep Flow Technique (DFT) is a hydroponic method that provides nutrients in the form of water in the form of a pool. DFT hydroponic cultivation of plants, especially pakcoy (Brassica rapa L.) can increase income, can be consumed alone at home, adds nutritional value, and can prevent stunting. The problem of stunting can be prevented by consuming nutritious food, one of which is by consuming vegetables. DFT hydroponic farming can be done in narrow areas, for example in yards, roofs, and so on. The purpose of this activity is to introduce DFT (Deep Flow Technique) hydroponics to pakcoy plants (Brassica rapa L.) as the main plant to the community in Kuta Blang Village, Samadua District, South Aceh District. This community service was carried out on Wednesday 17 November 2021. The method used in this community service was an extension method in the form of presentation of material and practices related to DFT hydroponics on pakcoy plants (Brassica rapa L.). The counseling process begins with the presentation of the material by the speaker, followed by discussion or question and answer.Keywords: Hydroponic Deep Flow Technique (DFT), pakcoy, stunting